Sifat Kimia Kayu Eboni pada Perbedaan Pola Strip dan Arah Radial (Chemical Properties of Diospyros celebica Bakh. in Different Streaks Pattern and Radial Direction) - Muhammad Asdar; Tibertius A Prayitno; Ganis Lukmandaru; Eny Faridah (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
The heartwood of ebony displayed series of axial and alternating black and paler streaks. Accordingly, ebony from Central Sulawesi was classified in two different streaks patterns i.e. SL (spider web) and batang macis (matches stick). We investigated the chemical properties (holocellulose, cellulose, lignin, extractive content, ash and pH value) of sapwood, intermediate, and heartwood from the different streaks patterns of ebony wood.  The mean value of holocellulose, cellulose, lignin, ethanol-toluena extractive,  hot water extractive, ash contents, and pH value were 76.59±3.02%, 50.62±4.86%, 26.72±3.05%, 9.71± 2.97%, 13.54±1.43%, 0.97±0.32%, 5.56±0.39, respectively.  On the basis of t-test, holocellulose, cellulose, and hotwater soluble contents were differed significantly between the two streaks patterns.  Analysis of variance showed the radial direction also affected significantly on the chemical contents.  The contents of the holocellulose, cellulose, lignin, extractive ethanol-toluen and ash were significantly differed among sapwood, intermediate and heartwood.  The heartwood showed higher levels of cellulose, lignin, ethanol-toluena extractive and ash contents than those of other parts.  On the contrary, the lowest levels of cellulose, lignin, and ash contents and pH value were found in the intermediate wood region.Keywords: chemical properties, Diospyros celebica, radial direction, spider web, streaks pattern